2014
DOI: 10.1007/978-3-642-41588-3_2
|View full text |Cite
|
Sign up to set email alerts
|

The Voltage Sensor Module in Sodium Channels

Abstract: The mechanism by which voltage-gated ion channels respond to changes in membrane polarization during action potential signaling in excitable cells has been the subject of research attention since the original description of voltage-dependent sodium and potassium flux in the squid giant axon. The cloning of ion channel genes and the identification of point mutations associated with channelopathy diseases in muscle and brain has facilitated an electrophysiological approach to the study of ion channels. Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 157 publications
(173 reference statements)
0
12
0
Order By: Relevance
“…Utilizing mutagenesis studies, we previously demonstrated that Na v 1.7-selective aryl sulfonamide inhibitors interact with the extracellular surface of the VSD region of DIV (McCormack et al, 2013;Alexandrou et al, 2016), although the precise mechanism for inhibition was not fully understood. Over the years, the use of polypeptide toxins has increased our understanding of the functional significance of the VSD of DIV in channel fast-inactivation (Catterall et al, 2007;Hanck and Sheets, 2007;Groome, 2014). Site-3 toxins, which include a-scorpion toxins and sea anemone toxins, bind to overlapping extracellular residues on the DIV S3-S4 loop, binding with highest affinity at negative membrane potentials where the channel is closed (Catterall et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing mutagenesis studies, we previously demonstrated that Na v 1.7-selective aryl sulfonamide inhibitors interact with the extracellular surface of the VSD region of DIV (McCormack et al, 2013;Alexandrou et al, 2016), although the precise mechanism for inhibition was not fully understood. Over the years, the use of polypeptide toxins has increased our understanding of the functional significance of the VSD of DIV in channel fast-inactivation (Catterall et al, 2007;Hanck and Sheets, 2007;Groome, 2014). Site-3 toxins, which include a-scorpion toxins and sea anemone toxins, bind to overlapping extracellular residues on the DIV S3-S4 loop, binding with highest affinity at negative membrane potentials where the channel is closed (Catterall et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The connection between Arg1457His and CMS affords an opportunity to better understand the mechanisms of voltage sensing and the nature of fast and slow inactivation processes in sodium channels. 39,40 There is a history of pathological Na v channel variation disrupting skeletal (eg, myotonias, periodic paralyses 23,25 ) or cardiac muscle (eg, long-QT or Brugada syndrome), 41 as well as neurons of the central nervous system and/or peripheral nervous system (eg, epilepsy, pain syndromes, congenital analgesia, anosmia, or other sensory deficits). [42][43][44][45][46][47][48] These pathogenic changes have provided a window into the basic functionality of these important channels, and in this report we add to this knowledge with the description of a residue of exceptional importance in fast inactivation, whose compromise results in a myasthenic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The biophysical basis for displacement of the gating charge, and thus voltage-sensitivity, is S4 translocation in response to altered membrane potential [reviewed by (Bezanilla, 2000;Bezanilla, 2018)]. Investigations of the role of the S4 segment as the voltage sensor have employed mutagenesis including mutant cycle analysis, toxins to trap resting or activated states, thiosulfonate reagents to determine S4 residue accessibility, fluorescence measurements, and molecular dynamics simulations [reviewed by (Groome, 2014)]. Pertinent to this review, a series of investigations have supported the premise that sequential, salt-bridge (countercharge/S4 residue) interactions facilitate transitions from the resting to fully activated state of VGICs.…”
Section: Vsd S1-s3 Negative Charges Contribute To Voltage-gating: Funmentioning
confidence: 99%